Americanizations of Holocaust Memory and Museum Aesthetic Experience - Karolina Krasuska (European Journal of American Studies)
The article interprets an emblematic segment of the United States Holocaust Memorial Museum exhibition, The Tower of Faces and the installation on the 1941-2 pogroms in Nazi-occupied Poland in the POLIN Museum of the History of Polish Jews to compare the aesthetic experience of these examples of Holocaust memorialization. It argues that using the concept of “Americanization,” as it is employed in American Studies in Europe and in Holocaust and memory studies, respectively, is instrumental in analyzing the museum experience and as such may contribute to the debates on POLIN and its representation of memory.